The relationship between teacher opinions and reported use of content area reading strategies among teachers on the Diploma in Education programme - Osborne, Annette (1990)
This study examines the relationship between teacher opinions regarding content area reading strategies and the reported use of such strategies in the local situation, in an effort to infer the extent of use of these strategies in the classroom. Questionnaires were administered to 55 secondary school teachers who participated in the Diploma in Education programme at The University of the West Indies, St. Augustine, during the 1988/89 academic year. Analysis of the data indicated a modest correlation between opinions and the reported use of these strategies in Trinidad and Tobago, which is positive and moderately high
Keywords: Secondary school students